Rancang Bangun Alat Elliptical trainer Outdoor - Zainal Arifin; Singgih Dwi Prasetyo; Suyitno Suyitno; Dominicus Danardono Dwi Prija Tjahjana; Rendy Adhi Rachmanto; Wibawa Endra Juwana; Chico Hermanu B. Apribowo; Trismawati Trismawati (Universitas Sebelas Maret, 2020)
The placement of outdoor fitness equipment at tourist attractions is one of the attractions for tourists. Besides that, it can also be used as a means of health socialization for the community in public places. The elliptical trainer type air walker is a popular fitness tool because it is easy to use and has a small risk of injury. Elliptical trainer has a working principle like a walking person where movement is influenced by the force of the hand and leg movements. The design of an elliptical trainer fitness equipment that will be placed in a public place needs to be done to get a good level of security. This article discusses the design of an elliptical trainer device that is safe to place outdoors. The design process uses the Solidworks 2017a application. The elliptical trainer is divided into 4 parts, namely the main frame, drive shaft, hand handle, and leg handle. The manufacturing process is carried out based on Design Manufacture and Assembly and machinery to reduce the risk of manufacturing failure and make it easier to work on. The result of the elliptical trainer design has dimensions of 2,500 x 1,800 x 1,000 mm. The main frame has a safety factor of 3 with a displacement of 8,524e-7 mm.